City Branding Strategy on the Evaluation of Tourism Destination Problems in Rural Area (Evidence from Pasuruan City, Indonesia) - Yusuf Risanto; Ida Yulianti (Program Pascasarjana, 2016)
This research find the essential problems of tourism destinations in rural area in Pasuruan City, Indonesia. Based on the phenomenology method and using an open questionnaire, researcher make a deep interview with manager of 10 tourism destinations in Pasuruan city relating with their condition. All of the tourism destinations sample in this research represent four tourism destinations categories includes natural, cultural, agricultural and special destinations. In general the essential problems was meet by most of the tourism destinations are poor management system, unspesific additional facilities, and no innovative marketing strategy. In the evaluation of this problems, city branding strategy is offered to cover a comprehensive solution. The main dimensions of city branding strategy for this problems are green space branding, identifiable image and positive brand experience.Keywords: City Branding, Rural Area, Tourism Destinations.